A new genus and species of Bruchinae, with a key to the genera from Australia (Coleoptera: Chrysomelidae) - Reid, Chris A. M.; Beatson, M. (Zootaxa, 2013)
A new genus of Bruchinae, Buburra Reid & Beatson, is erected for a single new species, B. jeanae Reid & Beatson. Buburra is endemic to Australia where it is known from a single site at high altitude in Victoria. The hostplant is unknown. Buburra is placed in the tribe Pachymerini. A key is provided for identification of the 12 genera of Bruchinae in Australia, including Caryotrypes Decelle, 1968, recorded from Australia for the first time. Five Australian species described in Bruchus Linneus, 1767, are newly transferred to Bruchidius Schilsky, 1905: Bruchidius diversipes (Lea, 1899) comb. nov.; B. maestus (Lea, 1899) comb. nov.; B. oodnadattae (Blackburn, 1900) comb. nov.; B. persimulans (Blackburn, 1900) comb. nov.; B. quornensis (Blackburn, 1900) comb. nov. A checklist is provided for the species of Bruchinae in Australia.